ANALISIS BEBAN KERJA MENTAL DENGAN MENGGUNAKAN METODE NASA-TLX DAN MASLACH BURNOUT INVENTORY PADA PT. XYZ (STUDI KASUS EKSITU DUMPING KALIMANTAN TIMUR) - Raihan Ahmad Widiarto, (2023)
The performance and productivity of individuals and organizations are greatly affected by workload. Excessive workload can be a serious problem for employees and organizations in an increasingly complex and dynamic world of work. Excessive workload can cause stress, burnout, and even workplace accidents, as well as affect the mental and physical health of employees as well as the quality and safety of goods and services produced by the company. Performance is affected by workload, workplace, and fatigue level. The purpose of this study was to identify factors that affect the level of fatigue of teams working on eksitu dumping activities at PT. XYZ. In this study, there were three variables, with their respective sub criteria: workload, fatigue level, and work environment. In this study, the subjects were all members of the eksitu dumping crew operating on the Balikpapan ship, totalling 32 people. To find out if Maslach's burnout inventory method affected worker burnout, the data was analyzed using NASA-TLX and Borg CR10. The results showed that mental load is a component that has an influence on the level of burnout of workers in dumping.